Organisational Stress and Stress Management Mechanism Among police personnel: A Case Study (International Journal of Food and Nutritional Sciences, 2022)
With varying intensity and dimensions every individual has some extent of stress. Stress has emerged as a critical and most important issue in today’s era for the people possessing busy and hectic lifestyle. Organisational Stress (OS) is one which any individual experience because of the factors related to the work in the organisations. Stressors on policemen are not unique as compared to the people working in the society which has become global issue and needs immediate interventions to save lives of police personal. Increasing incidence of organisational stress among police personnel is a great concerned. The evident studies and reports of the Bureau of Police Research and Development have highlighted that a greater number of policemen die every year due to increasing stress as compared to deaths due to other reasons. Thus, this study encompasses various aspects related to organisational stress among police personnel in Satara police and to find out the various stress management mechanisms used by them for relieving their organisational stress.